The Selfie of the Year of the Selfie: Reflections on a Media Scandal - Miltner, Kate; Baym, Nancy (International Journal of Communication, 2015)
At 11:00 a.m. on December 10, 2013, the French newswire service Agence France-Presse tweeted a photo of Danish Prime Minister Helle Thorning-Schmidt taking a selfie with U.S. President Barack Obama and UK Prime Minister David Cameron during Nelson Mandela’s memorial service. Thirty-nine minutes later, media gossip website Gawker had picked up the photo, followed swiftly by news outlets around the world. By the next day, the image was Agence France-Presse’s second most downloaded photo from the memorial, second only to the image of Barack Obama and Raul Castro exchanging a historic and controversial handshake (“Photo of Thorning’s Selfie,” 2013). The Washington Post declared it the seventh-best political photo of 2013 (Cilizza, 2013).